The quality of nursing care in the palliative field - Mar Zulueta Egea; María Prieto-Ursúa; Laura Bermejo Toro (Universidad de Alicante, 2019)
Care is the essence of the nursing profession and takes full meaning in the field of palliative care. Palliative nursing acquires an important role in the relationship with the patient and/or family and accompaniment in suffering. Analysing whether there is quality or not in the nursing care provided to the patient with terminal illness and his family, helps to build continuous improvement and professional excellence. The aim of our study is to carry out a theoretical review on the quality of nursing care in the field of palliative care. For this purpose, we worked with the databases Academic Search Complet, PsycInfo, CINAHL, CUIDEN and MEDLINE. The results indicate that the quality of nursing care seems to be a poorly researched field, and that the instruments of measurement evaluate the perceived quality from patient satisfaction, only in the hospital setting. There is a broad consensus on the essential dimensions for assessing the quality of palliative care, but no scales have been found that specifically measure the quality of nursing palliative care. Quality is therefore evaluated through advanced nursing competencies and nursing professional values in palliative care